My week with him - Goffney, Joya (HarperTeen, an imprint of HarperCollins Publishers, 2023)
"Nikki can't wait to leave Texas and follow her dreams of a music career... After a painful betrayal by her sister and a heated argument with their mother, Nikki is kicked out and finds herself homeless. She decides to go to California to pursue her singing career. When her best friend, Malachai, discovers her plan to flee Texas, he begs her to spend the remainder of spring break with him. He believes that over the course of a week, he can convince her to stay in Texas, or to at least graduate high school. But their plans are interrupted when Nikki's little sister Vae goes missing. Nikki is forced to work alongside her difficult mother as they set off in search of Vae, with Malachai's support. Will Nikki find a reason to stay in Texas, or will this spring break be the last time she sees them? Through her emotional journey, Nikki ultimately finds the love she's always been missing and discovers the power of her own voice"--Provided by publisher.